Life-time tobacco consumption and oral cancer among citizens of Karachi: one of the world’s highest reported incidence areas for oral squamous cell carcinoma - Muhammad Mohiuddin Alamgir; Fouzia Shaikh (Journal of the Pakistan Medical Association, 2021)
Objective: To analyze dose-response relationship between the common risk factor of tobacco consumption and oral lesions like squamous cell carcinoma and pre-cancerous lesions. Methods: The study comprises of 150 histologically confirmed OSCC cases, 100 cases of clinically diagnosed oral pre-cancerous lesions and 108 habit-matched controls. Life-time tobacco-exposures were calculated as tobacco indices, i.e., chewing index and smoking index, for comparison between cases and controls. Results: The age of OSCC cases ranged from 20-78 years and pre-cancerous cases from 16-78 years, mean 47.1 ± 12.22 and 34.17 ± 13.78, respectively. Of all OSCC patients 125 (83.33%) and 96 (96%) of PCL patients gave a positive history of tobacco use. 68.8% of all 250 cases were exclusive tobacco chewers which turned out to be the most prevalent tobacco habit. Exclusive smoking was seen in 11 (4.4%) cases, 38 (15.2%) patients had a mixed tobacco habit of chewing plus smoking while 29 (11.6%) were tobacco free. Tobacco indices (median values) in exclusive chewer’s category were found to be lower in cancers (150) as compared to matched controls (210) but were nearer to pre-cancers (144). In pre-cancers we found lower median values of tobacco indices for all chewers, exclusive chewers and all-smokers categories in comparison to controls, i.e., 144/200, 144/210, 10/21 respectively. Conclusion: Life-time tobacco exposure indices were either comparable or lower in studied patients as compared to controls pointing towards the role of other etiological factors in addition to tobacco for malignant transformation of oral mucosa. Continuous...